Evaluasi Pengaruh Tie-Up Peledakan Terhadap Getaran Pada Penambangan Batu Granit PT Mandiri Karya Makmur Di Desa Tanjung Gunung Kecamatan Pangkalanbaru: The Evaluation Blasting Tie-Up Effect of Vibration in Granite Rock Mining of PT Mandiri Karya Makmur Tanjung Gunung Village Pangkalanbaru District - Lenny, Lenny; Irvani, Irvani; Akuan, Abrianto (MINERAL, 2016)
PT Mandiri Karya Makmur is a private mining company that mine granite rock located in CentralBangka Regency Area.The main activity in extracting granite rock was conducted using blastingmethod. Blasting acitivy could influence invironment around mine site, including community.Therefore, it was necessary to evaluate blasting activity, especially tie-up to decrease vibration fromblasting activity itself. The method used to make design of tie-up was using shotplus-i program. Theaims in this research was to set up surface delay and the use of time window in order to determineamounts of similar blasting holes. The data used including sounding data and blast design todetermine PPV value. The value was calculated by using empirical formula of U.S.B of Mine No 656 of1971. The actual geometry used including burdens 1,8 m, spacing 2,3 m and hole depth rate 6 m.Then, determining the measurement of vibration was using Android based vibrometer. The result ofappropriate tie-up evaluation used in blasting was Box cut pattern, surface delay 25 ms and 42 mswith inisiation of left corner using time window 8 ms and similar blasting holes was 3 holes. Thisamount could minimize vibration. Actual PPV value was 0,7 mm/s, PPV recommendation value of 3,3mm/s and SD value of 19,6 m/kg. The cavacity of explosive was 932 kg and minimum safe distance of598 m from blasting point. It was categorised still safe referring to Building type theory of number 2(SNI 7571 : 2010).